A Trajetória Intelectual de Heleieth Saffioti e “A Mulher Na Sociedade de Classes” (1969), uma contraideologia a ordem patriarcal como ideia dominante - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
This research had as its object of study The Intellectual Trajectory of Heleieth Saffioti and “The Woman in Class Society” (1969), a conter ideology to the patriarchal as dominant idea. Saffioti was a precursor in the lines of research lines of studies concerning women and the capitalist system of production, from the use of the Marxist referential. The work that subsidized this research presents an analysis of the education/schooling of women, from the Colony to the Republic and the aggravating factors of this process for social inequalities, as well as the alienation of women in the capitalist society and the consolidation and institutionalization of the myth of women's inferiority. Although her academic production was focused on the analysis of the material conditions of society, it is worth noting that the scientific field was built on a male presence. Male intellectuals were present during Saffioti's academic and intellectual trajectory and that, in a way, influenced her production. Thus, we defend the thesis that thought on education and society is hegemonically male, but Heleieth Saffioti stood out with her intellectual production, discussing the condition of women in patriarchal society, and contributed to the educational area and to the Marxist production, broadening the debate. The temporal delimitation focuses on the decade from 1950 to 1960, which includes her training process in the Normal School, her entry in Social Sciences, her teaching in higher education and her free teaching with the production of "The Woman in Class Society", and the context of the military regime which was unfavorable to the Marxist production. The guiding question of this research is: How did the intellectuality of Heleieth I.B. Saffioti and consolidate and what was the contribution of her work "Women in Class Society" (1969) to Education? The general objective is to analyze the main moments in the life and academic and professional trajectory of Heleieth Saffioti, seeking to highlight, based on the work "Women in Class Society", the contributions to education. From this general objective derive the specific objectives that are: identify the formative and professional trajectory of Heleieth Saffioti and the reflections in her academic production; highlight the process of theoretical discussion of the work "Women in class society, by Marx and Engels; discuss the contributions of the work "Women in class society", by Heleieth I. B. Saffioti, to the area of education. This research has as its theoretical basis the works of Engels (2010), Marx (2002, 2009, 2011), Marx and Engels (1978, 1977, 2007), Faoro (2001), Fernandes (2008), Tristán (2015), and the publications of Saffioti (1976, 1987). From the methodological point of view, this research has a bibliographical and documental character. The sources used in this research were the bos, articles by Heleieth Saffioti, understood as products of a certain time, written by historical subject who occupied specific positions. The study showed that Heleieth Saffioti unveiled in her work the relationship between capitalism and patriarchy, patriarchy being prior to capitalism. Her contributions to education are the socially constructed discriminatory marks being elaborated by a set of dimensions.
Keywords: Estado-Educação-Igreja; Mulheres-intelectuais; Heleieth Saffioti; Marxismo-patriarcado-capitalismo; Education-Church; Women-intellectuals; Heleieth Saffioti; Marxismpatriarchalism-capitalism; CNPQ::CIENCIAS HUMANAS::EDUCACAO